Crushing and grinding at Bond Gold’s Colosseum mine : An update - R. L. Beatty (Society for Mining, Metallurgy & Exploration, 1989)
Bond International Gold's Colosseum gold mine was discovered in 1865. No recorded production occurred, however, until the 1930s, with production of about 19 kg (615 oz) of gold. The mine was closed in 1942 as a nonessential industry during World War II. The property was acquired by Dallhold Resources in mid-1986. Construction of a 1.1-million Mt (1.2-million st), carbon-in-pulp (CIP), cyanide mill began in November 1986 and was completed in September 1987. Minable reserves are estimated to be 9.5 Mt (10.5 million st), with an average grade of 2.1 g/t (0.061 oz per st). This article describes the general process flow and plant equipment. And it looks at the maintenance and operational problems encountered in the first six months of operation. Process description Ore is direct hauled from the open-pit mine 1.5 km (1 mile) to the crushing facility. There it is crushed to -152 mm (-6 in.) with a single- stage, 1.5-m x 1.2-m (60-in. x 48-in.), 186.5-kW (250-hp), Fuller-Traylor jaw crusher. The ore is then stockpiled in a 31.7-kt (35,000-st) reclaim ore pile. Lime is added to the crushed product as it is conveyed to a single 6.4-m x 4-m (21-ft x 13-ft), Hardinge semiautogenous grinding (SAG) mill, followed by a single 4.3-m x 7.3-m (14-ft x 24-ft) Hardinge overflow ball mill. After grinding, the slurry is thickened and then preaereated for three hours. Following preaereation, the pulp is leached with NaCN at a pH of 11, also for three hours. The slurry then goes through a seven-stage CIP circuit for 21 hours. Then the tailings slurry is preaereated for three hours before cyanide destruction using the Inco process. Loaded carbon is eluted using an Anglo American strip, followed by electrowinning on stainless steel wire. The stainless steel wire is transferred to refinery cells where the gold and silver is plated on stainless steel plates. Following electrore-fining, the gold-silver foil is removed, melted, and poured into dore bars for shipment. The crushing, milling, refining, and maintenance processes require 37 people. Crushing The crushing area required changes and modifications following start-up. Several areas are of specific note. Structural failures Rubber support cushion blocks located under the coarse ore bin failed. These were replaced with heavier, more durable blocks and have since appeared to be satisfactory. A severe structural vibration was encountered in the entire crushing facility. A mechanical engineer, brought in by the contractor, determined the structure needed more support and cross-bracing.